1995
DOI: 10.1093/clinchem/41.5.731
|View full text |Cite
|
Sign up to set email alerts
|

Direct determination of lipoprotein(a) cholesterol by ultracentrifugation and agarose gel electrophoresis with enzymatic staining for cholesterol

Abstract: Lipoprotein(a) [(Lp(a)], a low-density lipoprotein (LDL)-like particle, contains in addition to LDL a specific protein component, apolipoprotein(a) [apo(a)]. Conventionally, Lp(a) has been measured by immunological methods that distinguish between Lp(a) and LDL by dealing with apo(a) as an antigen. We describe a new method to determine Lp(a) on the basis of its cholesterol content. Very-low-density lipoproteins were removed from serum by preparative ultracentrifugation at a density of 1.006 kg/L. The infranate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
5

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 0 publications
0
6
0
5
Order By: Relevance
“…This Lp(a)-C assay is a high-throughput one and can be performed on 96-well plates or adapted for use with existing clinical analyzers using magnetic beads. The entire assay is completed within 1 h. Other Lp(a)-C assays have been described, including those using electrophoretic ( 17 , 18 ), single-density gradient ultracentrifugation ( 19 , 20 ), and affinity based on porous matrices using wheat germ agglutinin (which can bind glycoproteins such as apo(a)) ( 21 ) or polyclonal anti-Lp(a) serum ( 22 ). However, neither a gold-standard assay nor reference materials to standardize or harmonize Lp(a)-C assays currently exist.…”
Section: Discussionmentioning
confidence: 99%
“…This Lp(a)-C assay is a high-throughput one and can be performed on 96-well plates or adapted for use with existing clinical analyzers using magnetic beads. The entire assay is completed within 1 h. Other Lp(a)-C assays have been described, including those using electrophoretic ( 17 , 18 ), single-density gradient ultracentrifugation ( 19 , 20 ), and affinity based on porous matrices using wheat germ agglutinin (which can bind glycoproteins such as apo(a)) ( 21 ) or polyclonal anti-Lp(a) serum ( 22 ). However, neither a gold-standard assay nor reference materials to standardize or harmonize Lp(a)-C assays currently exist.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods to measure Lp (a)-C were previously reported. Nauck et al reported direct determination of Lp (a)-C by ultracentrifugation and agarose gel electrophoresis 25 ) . Sheman et al reported a measurement method with lectin affinity to isolate Lp (a) from other lipoproteins 26 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Plasma lipoproteins were separated by preparative ultracentrifugation and precipitation and cholesterol and triglycerides were assayed by enzymatic methods (Roche Diagnostics, Mannheim, Germany) (LRC Program, 1982). Lp (a) was determined with polyclonal antibodies (Inkstar, Stillwater, MN, USA) on a Behring nephelometer as described in detail by Nauck et al (Nauck et al, 1995). Apo E phenotyping was performed by agarose gel by isoelectric focusing and immunofixation as described previously (Luley et al, 1991).…”
Section: Biochemical Analysismentioning
confidence: 99%